Colombia : Review Under the Flexible Credit Line Arrangement. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses Colombia's Review Under the Flexible Credit Line (FCL) Arrangement. Growth is projected to remain robust in 2014 and beyond, although risks are tilted to the downside. Real GDP is projected to grow at around potential in 2014 and over the medium term, with inflation remaining within the target range of 2-4 percent. However, Colombia remains vulnerable to external risks, including a sharp decline in oil prices and a surge in global financial market volatility. The IMF staff assesses that Colombia continues to meet the qualification criteria for access to FCL resources, and recommends completion of the review under the FCL arrangement for Colombia.